DETERMINANTS OF SEXUAL ABUSE OF CHILDREN AT SERVICE CENTER OFFICES EMPOWERMENT OF WOMEN AND CHILDREN (P2TP2A) - Amini, Aisyah; Agustina, Agustina; Amin, Ghazali (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2023)
Background: The percentage of children around the world who experience physical or emotional abuse increases every year. Forms of harassment include murder, sexual acts, bullying, and enforcement of discipline that is too harsh. Sexual harassment that occurs in children in the city of Banda Aceh occurs every year. Data starts from 2014 (7 cases), 2015 (5 cases), 2016 (15 cases), 2017 (7 cases), 2018 (18 cases), 2019 (7 cases), and 2020 (31 cases). The aim of the research is to find out the determinants that influence the occurrence of sexual abuse in children. Method: This research uses descriptive analytical methods with a case control design. The data used is primary data and secondary data. The population in this study were children who experienced sexual abuse as a case group (31 children) and 31 children who did not experience sexual abuse (31 children) in Banda Aceh City. 31 cases and 31 controls. Data analysis used a logistic regression test with the SPSS version 22 program. Results: The research results obtained related variables, namely the role of parents (OR= 2.9; P=0.001), parental education level (OR=0.61; P=0.002 ), maternal knowledge regarding the introduction of the reproductive system at an early age (OR=3.2; P=0.0031), while variables that were not related to the occurrence of sexual abuse in children were the living environment (OR=2.3; P=0.097), family economy (OR=0.20; P=0.13), social media (OR=4.8; P=0.13). Suggestion: It is hoped that Service Centre Offices Empowerment of Women and Children (P2TP2A) office officers and the Banda Aceh City police can handle and optimize the prevention of cases of sexual abuse of children in Banda Aceh City and provide strict sanctions to perpetrators of sexual abuse so that it creates a deterrent effect and prevents them from committing such acts in the future.